JAK/STAT signaling regulated intestinal regeneration defends insect pests against pore-forming toxins produced by Bacillus thuringiensis - Wang, Zeyu; Yang, Yanchao; Li, Sirui; Ma, Weihua; Wang, Kui; Soberón, Mario; Yan, Shuo; Shen, Jie; Francis, Frederic; Bravo, Alejandra; Zhang, Jie (PLoS pathogens, 2024)
A variety of coordinated host-cell responses are activated as defense mechanisms against pore-forming toxins (PFTs). Bacillus thuringiensis (Bt) is a worldwide used biopesticide whose efficacy and precise application methods limits its use to replace synthetic pesticides in agricultural settings. Here, we analyzed the intestinal defense mechanisms of two lepidopteran insect pests after intoxication with sublethal dose of Bt PFTs to find out potential functional genes. We show that larval intestinal epithelium was initially damaged by the PFTs and that larval survival was observed after intestinal epithelium regeneration. Further analyses showed that the intestinal regeneration caused by Cry9A protein is regulated through c-Jun NH (2) terminal kinase (JNK) and Janus tyrosine kinase/signal transducer and activator of transcription (JAK/STAT) signaling pathways. JAK/STAT signaling regulates intestinal regeneration through proliferation and differentiation of intestinal stem cells to defend three different Bt proteins including Cry9A, Cry1F or Vip3A in both insect pests, Chilo suppressalis and Spodoptera frugiperda . Consequently, a nano-biopesticide was designed to improve pesticidal efficacy based on the combination of Stat double stranded RNA (dsRNA)-nanoparticles and Bt strain. This formulation controlled insect pests with better effect suggesting its potential use to reduce the use of synthetic pesticides in agricultural settings for pest control.